2021
DOI: 10.15195/v8.a21
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of the Nones across the United States, 1973 to 2018: State-Level Trends of Religious Affiliation and Participation in the General Social Survey

Abstract: Although there has been a fast rise in the share of Americans reporting no religion, it is unclear whether this trend has affected different parts of the country equally. Against this backdrop, we apply dynamic multilevel regression and poststratification (Dynamic MRP) to General Social Survey data over the period 1973 to 2018 to estimate state-level religious trends. We validate our estimates against external benchmarks, finding that they perform well in terms of predictive accuracy. Substantively, we find st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The increase in the proportion of the U.S. population who do not identify with a religion in the past 30 years has been one of the more dramatic trends in social life (Burge 2020; Mitchell 2019; Wiertz and Lim 2021). Not all of these “nones,” of course, identify as atheists.…”
Section: Atheism As Identity And/or Worldviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the proportion of the U.S. population who do not identify with a religion in the past 30 years has been one of the more dramatic trends in social life (Burge 2020; Mitchell 2019; Wiertz and Lim 2021). Not all of these “nones,” of course, identify as atheists.…”
Section: Atheism As Identity And/or Worldviewmentioning
confidence: 99%
“…The increase in those who do not identify with religion in the United States (Burge 2020; Mitchell 2019; Wiertz and Lim 2021) has spurred research on possible causes of religious disaffiliation and adopting nonreligious identities. Berger (1967) suggested that in religiously pluralistic contexts, all religious worldviews become less plausible.…”
Section: Religious Doubt and Adopting An Atheistic Worldviewmentioning
confidence: 99%
“…Finally, recent research has documented that many people, especially youth, are leaving the Church in droves (MacGregor & Haycook, 2021). Those who consider themselves religiously affiliated "nones" or "dones" have exploded in recent years across most of the major religious traditions, including the Catholic Church (Packard & Ferguson, 2019;Wiertz & Lim, 2021). Fewer church attendees mean less financial resources, closed or merged parishes, and much belt tightening that affects everyone who works for the Church.…”
Section: Why Are Catholic Workers At Elevated Risk For Burnout?mentioning
confidence: 99%
“…While stress has increased, religious engagement has dramatically decreased in recent years. More Americans, for example, consider themselves unaffiliated with any religious or spiritual tradition or community (Twenge et al, 2016;Wiertz & Lim, 2021). Fewer people report attending religious services on a regular basis and more people identify as either atheist or agnostic (Rosmarin & Koenig, 2020).…”
mentioning
confidence: 99%